Seizure as Early Presentation of a Pneumocephalus after Cochlear Implant: A Case Report - Palacios-García, José María (J Int Adv Otol, 2020)
Pneumocephalus after cochlear implantation is very rare with five reported cases in the literature. The presence of clinical features in the immediate postoperative period has never been reported, because they occur weeks after surgery. These neurological manifestations can compromise the patient’s life; thus, it is important to have proper knowledge and management of these manifestations. We present a case report with a review of the literature. A 35-year-old man began having seizures a few hours after a cochlear implantation. Computed tomography (CT) scan revealed a pneumocephalus and bone defect at the level of the electrode’s drilling path, not objected during the surgery. The patient was handled conservatively, and in subsequent reviews, CT objected reabsorption of the pneumocephalus. The presence of a pneumocephalus should be taken into account in the neurological features of a patient with cochlear implant, especially if mastoid bone defects are suspected during surgery. The management of the pneumocephalus will, in most cases, be conservative, consisting of clinical observation and imaging tests. Surgical treatment is reserved for situations in which the clinical manifestations are very symptomatic and when they are tension pneumocephalus.